Pelaksanaan Pembina Keamanan dan Ketertiban Masyarakat di Kepolisian Sektor Tapung - Masri (Jurnal Hukum Respublica, 2020)
The problem examined in this research is how is the implementation of Regulation of the Head of the National Police of the Republic of Indonesia Number 3 of 2015 concerning Community Policing on the main duties and functions and authority of Bhayangkara Community Security and Order in the Tapung Sector Police. This research method is carried out directly in the field according to the type of sociological legal research. The results showed that the implementation of regulations on Community Policing against the Tupoksi and the authority of Bhabinkamtibmas in the Tapung Sector Police has not achieved maximum results. Factors that hinder the implementation of regulations concerning Community Policing of the Tupoksi and the authority of Bhabinkamtibmas in the Tapung Sector Police are: applicable law, law enforcement officials, supporting facilities or facilities, community and cultural factors. Efforts taken are in the form of preventive and repressive measures.